Ultrasound-guided insertion of intra-aortic balloon counterpulsation in intensive care: description of the technique (2020)
Intra-aortic balloon counterpulsation (IAoBC) is a mechanical circulatory support device that has been used for more than 50 years, mainly for cardiogenic shock. Although its effect on mortality is controversial, IAoBC is still used in a wide variety of pre- and postoperative clinical settings in cardiac surgery centers. IAoBC has a complication rate of approximately 30%, mostly associated with problems during insertion and malpositioning. Thus, an insertion technique based on the use of ultrasound at the patient’s bedside in the intensive care unit (ICU) is proposed. © 2020, The Author(s).